Taxonomy and biostratigraphy of Ordovician brachiopods from northeastern Ny Friesland, Spitsbergen - Hansen, Jesper; Holmer, Lars E. (Zootaxa, 2011)
We describe Early and Middle Ordovician brachiopod faunas from northeastern Spitsbergen and discuss their biostratigraphical and palaeoecological implications. We recognise 60 species and 41 genera representing both linguliform and rhynchonelliform brachiopods. These include one new genus, the obolid Lenticulella with the type species Lenticulella amphora (Krause & Rowell, 1975), and 23 new species: Ectenoglossa? oviforma, Elliptoglossa vulgaris, Rosobolus? elongatus, Broeggeria obscura, Mirilingula? svalbardensis, Schizotreta marginalis, Conotreta convexa, Cyrtonotreta profilbekkiensis, Cyrtonotreta spinosa, Eurytreta subtriangularis, Hisingerella maniformis, Semitreta basisslettaensis, Semitreta pustulosa, Semitreta spitsbergensis, Numericoma? proclina, Eoconulus subquadratus, Dictyonites mugilis, Pelonomia sulcata, Leptella (Leptella) inequicostellata, Protoskenidioides promontorium, Anomalorthis rossi, Nothorthis subpyramidalis and Phragmorthis noda. The Ordovician succession contains both intertidal and deep-sea deposits with brachiopod faunas from nearly the whole range of environments. The Tremadocian is represented by a succession of low-diversity, rhynchonelli-6 · Zootaxa 3076 © 2011 Magnolia Pressform-dominated assemblages occupying shallow-marine environments. With the abrupt and large-scale drowning during the Floian, these faunas were replaced by a sparse slope fauna of micromorphic linguliforms. The outer shelf environments established in the latest Floian were occupied by a highly diverse brachiopod fauna dominated by micromorphic linguliform taxa. As the environment shifted toward the mid-shelf during the Darriwilian, however, the composition of the fauna changed to an Orthidiella-dominated assemblage of mostly rhynchonelliform taxa. The very late occurrence of the Orthidiella assemblage suggests that the Dapingian Orthidiella Zone found in America is probably diachronic. Although it includes many endemic species, the Middle Ordovician fauna shows a strong resemblance to the brachiopod fauna of Nevada. This study is based on approximately 16 500 brachiopod specimens obtained from both crack-out samples and acetic-acid-treated bulk samples.